Audit Committee and Tobin’s Q as a Measure of Firm Performance Among Nepalese Commercial Banks - Yadav, Ram Sagar; Silwal, Raman; Kilambu, Rasish; Shah, Ritika Kumari; Khadka, Rohit (Nepalese Journal of Business, 2024)
The study examines the impact of audit committee on the performance of Nepalese commercial banks. Tobin’s Q and return on assets are selected as the dependent variables. The selected independent variables are audit committee size, audit committee meeting, audit committee meeting allowance, gender diversity, board size and leverage. The study is based on secondary data of 16 commercial banks with 111 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, reports published by Ministry of Finance and annual report of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of audit committee size, audit committee meeting, audit committee meeting allowance, gender diversity, board size and leverage on the performance of Nepalese commercial banks. The study showed that board size has a positive impact on Tobin’s Q and return on assets. It implies that increase in board size leads to increase in Tobin’s Q and return on assets in Nepalese commercial banks. Further, gender diversity in the audit committee has a negative impact on Tobin’s Q and return on assets. This indicates that higher the number of females in the audit committee, lower would be the Tobin’s Q and return on assets. Similarly, the study showed that audit committee size has a negative impact on Tobin’s Q which indicates that increase in audit committee size leads to decrease in Tobin’s Q. Whereas, audit committee size has a positive impact on return on assets. It means that increase in audit committee size leads to increase in return on assets. Moreover, leverage has a positive impact on Tobin’s Q. It shows that higher the level of leverage ratio in the banks, higher would be the Tobin’s Q. However, leverage has a negative impact on return on assets indicating higher the level of leverage ratio in the banks, lower would be the return on assets.